The mutation rate and the age of the sex chromosomes in Silene latifolia - Krasovec, M; Chester, M; Ridout, K; Filatov, D (Cell Press, 2018)
Many aspects of sex chromosome evolution are common to both plants and animals [1], but the process of Y chromosome degeneration, where genes on the Y become non-functional over time, may be much slower in plants due to purifying selection against deleterious mutations in the haploid gametophyte [2, 3]. Testing for differences in Y degeneration between the kingdoms has been hindered by the absence of accurate age estimates for plant sex chromosomes. Here, we used genome resequencing to estimate the spontaneous mutation rate and the age of the sex chromosomes in white campion (Silene latifolia). Screening of single nucleotide polymorphisms (SNPs) in parents and 10 F1 progeny identified 39 de novo mutations and yielded a rate of 7.31 × 10−9 (95% confidence interval: 5.20 × 10−9 − 8.00 × 10−9) mutations per site per haploid genome per generation. Applying this mutation rate to the synonymous divergence between homologous X- and Y-linked genes (gametologs) gave age estimates of 11.00 and 6.32 million years for the old and young strata, respectively. Based on SNP segregation patterns, we inferred which genes were Y-linked and found that at least 47% are already dysfunctional. Applying our new estimates for the age of the sex chromosomes indicates that the rate of Y degeneration in S. latifolia is nearly 2-fold slower when compared to animal sex chromosomes of a similar age. Our revised estimates support Y degeneration taking place more slowly in plants, a discrepancy that may be explained by differences in the life cycles of animals and plants.